Stem: associated features in tumor cells able to colonize secondary tumor sites - Valenzuela Alvarez, Matias Juan Pablo (2019)
Osteosarcoma (OS), the most frequent bone tumor in pediatrics, presents critical clinical challenges in lung metastasis and chemoresistance emergence. Understanding OS switch into a metastatic phenotype and the interaction OS-stromal cells relevant in the new niche, would help in developing better diagnostic and therapeutic tools. In order to distinguish aspects that would allow OS cells to leave the bone niche and survive in a new tissue environment, we evaluated behavioral features acquired by OS cells with ability to establishsecondary tumor growth in the lungs, approaching the degree of differentiation, doxorubicin (doxo) exclusion and distribution properties and molecular signatures. Our results indicate that lung-colonizing OS cells diminished its osteoblastic potential while modified the intracellular localization of chemodrugs. In this way, doxo switched from a nuclear to a cytoplasmatic distribution in cells with lung colonizing ability (0,884±0,015 SAOS2;0,546±0,131 LM7). These features coincided with a higher level of expression of stemrelated genes and lower expression of differentiation-associated markers even at basal conditions in the metastatic cells. On the other hand, the higher osteogenic activity of OS cells with non-colonizing features was even reflected as a paracrine osteo-inductive effect. In addition, OS cells with high and low lung-colonizing capacities have opposite impact in mesenchymal stem cells (MSCs). Further, OS cells colonized-mouse lungs had a greater chemoattractive induction on MSCs. A major acquisition in tumor cells with metastatic features is a switch into a stem-like state that could favor their survival in the pulmonary niche, opening new possibilities for specific chemotherapeutic schemes. We provide new insights on OS cells differing in lung homing ability, with particular emphasis on multidrug resistance and interaction with MSC, which would impact in early diagnosis and therapeutic management.